2015
DOI: 10.1016/j.ijhydene.2015.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack initiation and growth in a CrMo steel under hydrogen pressure

Abstract: International audienceAlong the hydrogen supply chain, metallic components, such as pressure vessels, compressors and valves, are facing high pressure hydrogen gas. The object of this paper is to address microstructural as well as mechanical aspects of fatigue crack initiation and growth at room temperature in a quenched and tempered (Q&T) low alloy steel under hydrogen pressure in the range 0.5e35 MPa. For such steel, the need to perform tests in-situ under hydrogen pressure is required. The influence of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…There are many studies that have been performed on this topic. Briottet et al studied the fatigue crack initiation and growth in Cr–Mo steel under hydrogen pressure and indicated that, with increasing hydrogen pressure, the number of cycles needed to initiate crack formation decreased [ 7 ]. Garcia et al studied the effect of hydrogen on the tensile properties of CrMoV steels by means of the small punch test, and found that the CrMoV steel has a high susceptibility to HE [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies that have been performed on this topic. Briottet et al studied the fatigue crack initiation and growth in Cr–Mo steel under hydrogen pressure and indicated that, with increasing hydrogen pressure, the number of cycles needed to initiate crack formation decreased [ 7 ]. Garcia et al studied the effect of hydrogen on the tensile properties of CrMoV steels by means of the small punch test, and found that the CrMoV steel has a high susceptibility to HE [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of striations is not influenced by hydrogen (Kanezaki et al, 2008). Nevertheless, many authors have reported difficulties in detecting striations in fracture surfaces influenced by hydrogen (Liu and Atrens, 2017;Colombo et al, 2016;Briottet et al, 2015). Therefore, this result was expected even though it can not be explained using past literature.…”
Section: Crack Propagationmentioning
confidence: 72%
“…Several authors have proved that hydrogen accelerates this crack nucleation process that reduces the fatigue life of steel. Briottet et al (2015) found a strong decrease in the number of cycles to crack initiation for steel 25CrMo4 (quenched and tempered). Specimens tested in a hydrogen environment showed a reduction in cycles to crack initiation of 10, relative to specimens tested in air.…”
Section: Hydrogen Induced Acceleration Of Fatigue Crack Initiationmentioning
confidence: 95%
See 2 more Smart Citations